Integrasi Algoritma RSA (Rivest Shamir Adleman) dan Caesar Cipher untuk Meningkatkan Keamanan Enkripsi SMS (Short Message Service) - Yosanny Ferdino Rizkyansyah; Aries Saifudin (Jurnal Informatika Universitas Pamulang, 2018)
SMS (Short Message Service) is used because it is cheap, easily accessible and a popular method to sent information by a text message using a mobile phone. However, the original SMS application on android phones are have no security features. A message sent is still in plain text form so easily be intercepted without unknown by the sender or the recipient. Therefore, proposed encryption algorithm RSA (Rivest Shamir Adleman) and Caesar Cipher to secure a text message sent. The results showed that the application can prevents the contents of SMS to intercepted or viewed by unauthorized people because the message that is sent is not in plain text, but the message has been encrypted (cipher text).